2017
DOI: 10.1021/acs.estlett.7b00168
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Electrochemical Current Accelerates Urea Hydrolysis for Recovery of Nutrients from Source-Separated Urine

Abstract: This study demonstrates that a wastewaterdriven microbial electrochemical process greatly facilitates traditional rate-limiting urea hydrolysis and efficiently recovers ammonium and phosphate nutrients from source-separated urine. Using both synthetic and diluted actual urine and wastewater, 76−87% of nitrogen and 72−93% of phosphorus were continuously removed from source-separated urine and collected in recovery solutions. The acceleration of hydrolysis and nutrient recovery were driven by the electrical pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…MMFC are widely investigated to recover N III from wastewater [ 113 ], landfill leachate [ 82 ] and urine [ 114 , 115 , 116 ], where the conversion of urine to ammonium via ureolysis is accelerated by a generated electric field. The presence of CEM and AEM in such cells makes it possible to separate P V (which is in the form of phosphoric acid anions) and NH 4 + cations.…”
Section: Modern Trends In Nutrients Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…MMFC are widely investigated to recover N III from wastewater [ 113 ], landfill leachate [ 82 ] and urine [ 114 , 115 , 116 ], where the conversion of urine to ammonium via ureolysis is accelerated by a generated electric field. The presence of CEM and AEM in such cells makes it possible to separate P V (which is in the form of phosphoric acid anions) and NH 4 + cations.…”
Section: Modern Trends In Nutrients Recoverymentioning
confidence: 99%
“…The second one is a periodic cleaning of membranes using acids, alkalis, perchlorates, and other oxidizing agents [ 90 ] or enzymes [ 9 , 114 , 247 , 248 , 249 ]. Xue et al [ 90 ] clearly demonstrated the effectiveness of such treatment ( Figure 25 ).…”
Section: Innovations In Nutrient Recovery Processes With Ion-exchange...mentioning
confidence: 99%
“…Urine as the liquid metabolites of mammal makes up only about one percent of the total domestic wastewater (DWW) volume, but it contributes to nearly 80% of nitrogen and 50% of phosphorous in DWW [1]. Direct discharge of untreated urine not only causes water pollution but also causes potential infections by pathogens in urine [2].…”
Section: Introductionmentioning
confidence: 99%
“…The CEM divided cell electrolytic reactors have been reported to separate and concentrate NH + 4 from synthetic wastewater (Gildemyn et al, 2015;Ren et al, 2017), urine (Luther et al, 2015), and anaerobic digestate (Desloover et al, 2015). The AEM divided cell reactors have been reported for phosphate (PO 3− 4 ) recovery (Zhang et al, 2013;Chen et al, 2017;Ledezma et al, 2017;Ren et al, 2017). NH + 4 and PO 3− 4 recoveries up to 90% have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%